Pengembangan Kelompok Sadar Lingkungan Berbasis Ecobrick sebagai Langkah Awal Pengolahan Sampah: - - Indra Fauzan; Adil Arifin; Suci Rahmadani; Irmayani, Tengku; Perdana Nasution, Zaid (Yayasan Literasi Sains Indonesia, 2023)
The global problem that has not yet been resolved is related to waste, which continues to increase, especially in coastal areas. One of them is in Indonesia, precisely in Bagan Arya Village, Batu Bara Regency. Apart from household production waste, there is also a lot of waste sent from the sea. To tackle the accumulation of waste, an environmentally conscious group was formed to manage ecobrick-based waste. However, the group's limited knowledge, such as the difficulty of drying waste, assembling ecobrick products, and providing education to the community in Bagan Arya Village are things that need to be resolved. The methods applied in implementing this service start with strengthening Environmental Awareness Group materials, product assembly training, and waste drying training. The results of this service include the implementation of several trainings such as training on drying waste using drying nets, training on making ecobrick products using wire as product adhesive, strengthening ecobrick-based waste processing materials to increase the knowledge of environmentally conscious groups, as well as carrying out outreach to the community in Bagan Arya Village. about the importance of keeping the environment clean.